The family Nyctaginaceae (Caryophyllales) in Sonora, Mexico - Sandoval-Ortega, Manuel Higinio; Sánchez-Escalante, José Jesús (Phytotaxa, 2022)
The family Nyctaginaceae comprises 7 tribes, 31 genera and 300–405 species distributed in the tropics and other warm regions of the world, and in Mexico, it has been studied mainly in the central-southern zone of the country. The aim of this work is to report the genera and species of Nyctaginaceae found in Sonora. The material collected in the state of Sonora and deposited in University of Sonora Herbarium and Mexico National Herbarium was reviewed and corroborated using the literature. The specimens deposited in the Arizona State University Vascular Plant Herbarium, University of Arizona Herbarium, Desert Botanical Garden and other collections, were also consulted using the platform Red de Herbarios del Noroeste de México. In the state of Sonora, the family Nyctaginaceae is represented by 11 genera and 33 species. All are native. A dichotomous key for the genera of Nyctaginaceae in Sonora is provided and the types of 23 names are here designated.